Strategic Issues in Dam Operation and Maintenance in Indonesia - Abdul Malik Sadat Idris; Angga Sukmara Christian Permadi; Unika Merlin Sianturi; Frieda Astrianty Hazet (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
Strategic issues in dam operation and maintenance are important to meet domestic water needs and the study was conducted by the Dam Operational Improvement and Safety Project (DOISP) in two phases. DOISP Phase I was established to continue the Dam Safety Program with the focus on the operational improvement and the safety of dams. The Dam Operational Improvement and Safety Project Phase II (DOISP Phase II) is a continuation of DOISP Phase I that previously has provided support to the completion of remedial and rehabilitation works and operational and safety improvement of 34 dams owned the Ministry of Public Works and Housing (MPWH) as well as the preparation of various guidelines which relate to the dam management operation. Strategic issues in operation and maintenance are prepared in 2020-2024, strategic plan by the Directorate of Water Resources and Irrigation (Ministry of National Development Planning/Bappenas). Planning based on strategic issues in operation and maintenance is important because a dam and reservoir can support hydropower, navigation, recreation, flood control, irrigation, and water supply, with each multipurpose benefit having a significant social and economic impact at the local level, regional and national.